2022
DOI: 10.3390/su14063557
|View full text |Cite
|
Sign up to set email alerts
|

What Type of Households in Mongolia Are Most Hit by COVID-19?

Abstract: The study aims to validate the measures taken by the government of Mongolia against COVID-19 and to analyse the negative impacts of COVID-19 on the livelihood of different types of households. The survey covers 362 households consisting of five different types, namely, apartment households, ger district households, herder households, vegetable growing households, and small farmer households. Principal component analysis is used to reduce the number of variables to a few factors that best explain the variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Away from national centres, excluded from global (tourism) fows, family and community self-reliance grew. With some State fnancial assistance (Mongolia; see also Gombodorj and Pető 2022) and without any of it (Talek, Kalacha, and Rombo in Kenya), herders expressed pride in their capacity to solve problems autonomously. Counter-intuitively too, the lockdown stimulated socialization and collective action, with people coming together for events and worshipping, organizing 'bush markets' and long-distance trade (Kenya), and feeding urban centres (Mongolia).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Away from national centres, excluded from global (tourism) fows, family and community self-reliance grew. With some State fnancial assistance (Mongolia; see also Gombodorj and Pető 2022) and without any of it (Talek, Kalacha, and Rombo in Kenya), herders expressed pride in their capacity to solve problems autonomously. Counter-intuitively too, the lockdown stimulated socialization and collective action, with people coming together for events and worshipping, organizing 'bush markets' and long-distance trade (Kenya), and feeding urban centres (Mongolia).…”
Section: Discussionmentioning
confidence: 99%
“…The frst divide lies between rural and urban areas. At national levels, Kenyan and Mongolian (agro)pastoralists had zero COVID-19 cases in those early days, mostly felt safe, and were generally more food secure than urban residents (see also Gombodorj and Pető 2022). Relying on natural resources has been a key lockdown coping strategy of dryland rural communities (Krauss et al 2021), which depends on access to land and secure tenure rights (Walters et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In March 2020, the GoM introduced restrictions in response to the COVID-19 pandemic, with the first documented case of locally transmitted COVID-19 infection detected in November 2020. 10 Additional details on the COVID-19 pandemic response in Mongolia can be found in Appendix p 1.…”
Section: Methodsmentioning
confidence: 99%
“…Chetty, Friedman, Hendren, Stepner, and the Opportunity Insights Team (Chetty et al 2020) estimated spending of the US households and found that the initial impacts of COVID-19 on economic activity were largely driven by a reduction in spending by higher-income individuals due to health concerns, which in turn affected businesses that cater to the rich and ultimately reduced the incomes and expenditure levels of low-wage employees of those businesses. Gombodorj and Petö (Gombodorj, Petö 2022) cited that in the United States and the United Kingdom, the least educated women are those who suffer most from the consequences of the pandemic.…”
Section: Section 1 Introductionmentioning
confidence: 99%
“…In addition, they found that a decline in final consumption was more pronounced in FHHs than MHHs. Gombodorj and Petö (2022) have assessed the impact of Covid-19 by type of households in Mongolia and concluded that rural households, herders' families were less affected by COVID-19 than households in the capital city and other urban areas in terms of changes in their income and expenditure. But in their research gender of households was not fully specified.…”
Section: Section 1 Introductionmentioning
confidence: 99%